Reducing adverse events associated with the glucagon stimulation test for the assessment of growth hormone deficiency in adults with a high prevalence of pituitary hormone deficiencies. (28th March 2021) - Gogna, Reetu; Jung, Caroline; McLachlan, Kylie; Krishnamurthy, Balasubramanian; Hong, Alice; Derbyshire, Maresa; Kiburg, Katerina V.; Zacharin, Margaret; MacIsaac, Richard J.; Sachithanandan, Nirupa; Caputo, Carmela
Abstract: Design: A retrospective review of the adverse events (AEs) in 78 patients during the glucagon stimulation test (GST) for the assessment of growth hormone deficiency (GHD) before and after protocol amendments which aimed to reduce AEs in a group of patients with a high prevalence of pituitary hormone deficiencies. Patients: Based on our observations of frequent AEs during the standard GST protocol in an initial 25 patients (cohort 1), a modified protocol was introduced to include the routine administration of 20 mg of hydrocortisone pre‐GST in a subsequent 53 patients (cohort 2). Post hoc analysis of the effect of glucocorticoid dosing pre‐GST on AEs was examined in those receiving <20 mg hydrocortisone (group A, n  = 19) vs ≥20 mg hydrocortisone (group B, n  = 59). Measurements: AEs including hypotension, hypoglycaemia and nausea/vomiting. Results: Of the 78 patients undergoing the GST, 79% had ≥2 hormone deficiencies. Rates of AEs were 41% vs 30% for hypotension, 60% vs 28% for hypoglycaemia ( p  < .05) and 20% vs 13% for nausea/vomiting in cohort 1 compared with cohort 2, respectively. Post hoc analysis revealed lower rates of AEs in those receiving ≥20 mg hydrocortisone (group B) compared to those receiving <20 mg due to a reduction in hypoglycaemic events (82% vs 26%, p  < .001) and hypotension (50% vs 27%, p  = .05). Similar numbers of patients in group A and group B met criteria for GHD. Conclusions: In patients with a high prevalence of pituitary deficiencies, a modified GST protocol of additional stress dose glucocorticoid attenuated the frequency of AEs without appearing to compromise the performance of the GST.